Польські українці і українські поляки у львівській археології 1905—1945 років - Козловський, С.К. (Археологія і давня історія України, 2012)
Стаття присвячена постатям, долям та
взаємовідносинам польських і українських археологів, що мешкали та працювали на Галичині у
першій половині XX ст. Висвітлено загальновідомі
і маловідомі імена дослідників, що стояли біля витоків сучасної польської і української археології. Статья посвящена галицким археологам первой
половины ХХ ст., стоявшим у истоков современной
польской и украинской археологической науки.
Прослеживаются процессы становления ученых,
обучение в университетах, исследовательская и преподавательская деятельность во Львове, Кракове,
Варшаве, Праге, Вене и других центрах. Судьбы
исследователей рассматриваются на фоне сложных,
порой трагических, политических и социальных
событий того времени (распад империй, войны, революции, репрессии). Утверждается, что профессиональная львовская археология пережила в этот период два начала и две катастрофы. Освещаются
хорошо известные и малоизвестные личности, внесшие вклад в развитие археологической науки двух стран. The article touches upon the subject about Galician
archaeologists in first half of the twentieth century
wich stood behind the modern Polish and Ukrainian archaeology.
It traces the processes of scientists uprising,
university education, teaching and research activities
in Lvov, Krakow, Warsaw, Prague, Vienna and other
centers. Article covers researchers’ fates considered
on the background of complex and sometimes tragic,
political and social events of the time (the breakup of
empires, wars, revolutions, repressions). Author claims
professional Lviv archeology survived two start-ups
and two disasters within this period. Also well-known
and less-known personalities who developed the archaeology
of these two countries are highlighted.